Connectivity Among Populations of the Top Shell Gibbula divaricata in the Adriatic Sea - López-Márquez, Violeta; Templado, José; Buckley, David; Marino, Ilaria; Boscari, Elisa; Micu, Dragos; Zane, Lorenzo; Machordom, Annie (Frontiers in Genetics, 2019)
Genetic connectivity studies are essential to understand species diversity and genetic structure and to assess the role of potential factors affecting connectivity, thus enabling sound management and conservation strategies. Here, we analysed the patterns of genetic variability in the marine snail Gibbula divaricata from five coastal locations in the Adriatic Sea (central Mediterranean) and one in the adjacent northern Ionian Sea, using 21 previously described polymorphic microsatellite loci. Observed and expected heterozygosity varied from 0.582-0.635 and 0.684-0.780, respectively. AMOVA analyses showed that 97% of genetic variation was observed within populations. Significant genetic differentiation was found among nearly all of the pairwise FST comparisons. Three groups of populations were identified: eastern Adriatic populations, western Adriatic populations, and a third group represented by the single northern Ionian Sea population. Gibbula divaricata is thought to have a limited dispersal capacity related to its lecithotrophic trochophore larval stage. In fact, our results indicated that gene flow is mainly restricted along the coastline, with populations separated by the lack of suitable habitats or deep waters being almost isolated. Though the circulation system operating in this region certainly affects connectivity, our genetic analyses of Adriatic populations of G. divaricata suggest that the reproductive strategies and habitat requirements of this coastal species also play an important role in its population dynamics.